Efektivitas Pembelajaran E-Learning Berbasis Teknologi Digital Terhadap Peningkatan Kompetensi Mahasiswa Keperawatan: A Literature Review - Siti Zahara Nasution; Adelina Rizki Wardani Rangkuti; Evi Karota Bukit; Rika Endah Nurhidayah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction: The rapid advancement of information and communication technology has driven a major transformation in global nursing education systems. E-learning represents a learning approach that opens new opportunities for teaching and learning processes across various educational sectors beyond the conventional classroom setting. Nursing education demands comprehensive competency acquisition, encompassing cognitive, psychomotor, and affective dimensions. The acceleration of e-learning adoption became particularly evident during the Covid-19 pandemic, which forced all educational institutions to shift massively to online learning. This study aims to identify and analyze the effectiveness of e-learning on improving the competencies of nursing students. Methods: This study employed a literature review design using a systematic approach guided by the PRISMA framework. Articles were searched from three primary databases, ScienceDirect, PubMed, and Google Scholar covering publications from 2022 to 2026. Based on predetermined inclusion criteria, 10 primary articles were selected for data extraction and synthesis. Results: The review findings indicate that various digital technology-based e-learning platforms have been widely utilized in nursing education, including mobile- and multimedia-based competency evaluation systems, virtual simulation, online learning, immersive virtual reality (VR), LMS-based mobile learning, online cooperative learning methods, and Online Peer Assisted Learning (OPAL). Conclusion: The findings of this literature review indicate that digital technology-based e-learning is effective in enhancing the cognitive competencies of nursing students through flexible and self-directed access to learning materials.